Rasulullah Sebagai Role Model Ketaatan Yang Membentuk Pribadi Unggul - Ramadhani, Bintang Okta; Pinky, Dominik Hoki; Arjani, Nabil hukama Zulhaiba; Hilmayandani, Ricy; Wulandari, Sephia; Wismanto, Wismanto (Faidatuna, 2024)
Obedience to the Messenger of Allah is one of the fundamental obligations in Islam. This is not merely about compliance, but also about emulating the figure of Prophet Muhammad (SAW), who was sent as a mercy to all the worlds. The Prophet is not only presented as the bearer of the message but also as a tangible example of how humans should live, behave, and interact with one another and with their environment. Making him a role model in daily life means following the guidance that has proven to bring goodness and salvation in this world and the Hereafter.The purpose of this research is to understand the noble qualities of the Prophet, to inspire individuals to follow his example in worship, interaction with others, and to live with high values, thus forming individuals who are outstanding and have integrity. This research employs historical approaches, text analysis, case studies, and comparative studies. By using these methods, it is hoped that we can delve deeper into how the Prophet serves as a role model of obedience that shapes outstanding individuals.Prophet Muhammad (SAW) as a role model of obedience has a significant impact on the formation of exemplary characters. Through his exemplary conduct in obedience, morals, struggle, education, and social influence, he shapes outstanding individuals.